A Rare Case of Acute Infectious Purpura Fulminans Caused by Klebsiella Pneumoniae and Human Herpesvirus Type 5 - Li, Xiao-Lan; Luan, Chun-Yan; Fan, Ying-Jun; Lin, Xiao-Ying; Jiang, Dong; Su, Mei-Xian; Wang, Gang; Yang, Xu (Journal of inflammation research, 2022)
Background: Purpura fulminans (PF), a rare, life-threatening disorder, is a hematological emergency in which there is skin necrosis, disseminated intravascular coagulation (DIC), and protein C deficiency. In PF, the skin necrosis and DIC are secondary to protein C deficiency. This may progress rapidly to multiorgan failure caused by the thrombotic occlusion of small- and medium-sized blood vessels. Case Report: This article presents the case of a 22-year-old male with fever as well as necrotic and purpuric skin lesions. The ultrasound and computed tomography scans revealed infections in the skin wounds as well as venous microthrombosis and thrombosis in multiple intracranial and pulmonary vessels. The laboratory tests showed signs of sepsis, thrombocytopenia, an abnormal decrease in protein C and antithrombin III, DIC, multiple organ and system failures, gastric varices, and gastrointestinal hemorrhage. The blood, sputum, and secretions under the skin lesions were cultured and were positive for Klebsiella pneumoniae. The results of the high-throughput genetic testing of the pathogenic microorganism DNA were consistent. In addition, human herpesvirus type 5 was detected. The histopathological examination of the skin lesions revealed pathological features consistent with PF. After successful treatment by the departments of Dermatology, Emergency Critical Care Medicine, and the Intensive Care Unit, the patient was discharged after 67 days of hospitalization. Conclusion: Adults with acquired protein C and/or S deficiency states, including certain bacterial and viral infections, who drink alcohol and take varieties of non-steroidal anti-inflammatory analgesics at the same time, may develop acute infectious PF. Clinicians should be aware of this for early diagnosis and treatment. Keywords: acute infectious purpura fulminans, Klebsiella pneumoniae, human herpesvirus type 5, disseminated intravascular coagulation, multiple organ and system failures